Mitigating Precarious Employment in Quebec: The Role of Minimum Employment Standards Legislation - Bernstein, Stephanie (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
[A]ddresses Quebec's approach to reforming its Labour Standards Act. ...[E]xamines developments in Quebec in the early 2000s, with attention to efforts by the government to evaluate "atypical workers" in an attempt to mitigate precarious employment in this jurisdiction. --From editor's introductory chapter, p. 37.
Keywords: Labor Unions; Labor laws and legislation; Labor market; Temporary employment